Evaluation of Asprosin Hormone in Hypothyroidism Patients - Ateah, Nidaa; Y.Abed, Ahmed; A. Abed , Baydaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Asprosin was a novel adipokine that was released by white adipose tissue. It was activated by fasting and attracted to the liver, which allowed the liver to rapidly release glucose into the bloodstream. White adipose tissue was the source of asprosin. When people go on a fast, their blood sugar levels drop, which causes levels of the hormone asprosin to rise. It does this by binding to a G-protein-coupled receptor in the liver known as OR4M1, which in turn activates a cascade that involves the G -protein-cAMP-PKA pathway. Because of this, the glucose that is stored in the liver is released. We anticipate that by investigating the changes that occur in asprosin levels in hypothyroidism patients, we will be able to make a significant addition to the area and fill a gap that has been left unexplored in the anther researches. Eighty patients (women ) ranging in age from 25 to 65 were collected from the National Diabetes Center Al-Mustansiriyah University (Iraq) for the purpose of this study, which was designed as a cross-sectional study to determine the concentrations of serum ( asprosin, thyroid hormone T3 T4 TSH, Fasting blood glucose FBG, and lipid profile( Total cholesterol TCho,Triglycride TG,high density lipoprotein HDL, Low density lipoprotein LDL, Very low density lipoprotein VLDL) . In the period beginning in December 2021 and continuing until March 2022. This particular study included a total of 80 participants, 40 of whom had thyroid disease (hypothyroidism), and 40 healthy individuals who served as controls. When compared to the control group, the findings of this study indicate that the levels of total cholesterol TC, triglycerideTG, and low-density lipoprotein (LDL) have dramatically increased, whilst the levels of HDL have significantly decreased . A substantial increase in (Fasting blood glucose FBG and Body mass index BMI) levels was also observed, in contrast to the group that served as the control. In patients with hypothyroidism, the levels of thyroid-stimulating hormone TSH were considerably greater, while the levels of T3 were significantly lower. The T4 level, however, revealed no significant differences when compared to the control group. In addition, the level of asprosin was found to be high in the hypothyroidism group only contrast to the control group that participated in this research. This current study indicates the hormone asprosin could be helpful early diagnosis in monitoring hypothyroidism patients. hormone asprosin is a marker of glucose homeostasis, so it may be surrogate novel biomarker for all other traditional biomarkers for the prediction of risk factors of diabetes and thyroid dysfunction